Nutritional Status Psychiatric Patients Attending OPD at a Selected Tertiary Hospital - Sadhya, Gautam; Selimuzzaman, ABM; Islam, Rafiqul (TAJ: Journal of Teachers Association, 2010)
This descriptive type of cross sectional study was conducted among the psychiatric patients who had attended at the out patient department of psychiatry in Mitford Hospital Dhaka, with the objective of assessing the nutritional status of psychiatric patients. Mean age of the patients were 34.87 ±12.63 years. Of the total 150 patients, 56% were male and 44% were female. Among the study subjects, 54% were married, 30% unmarried, 10% divorced and 5% were widow. Regarding occupation, 12% of the patients were in service, 8.7% were students and 24.7% were unemployed. Among the psychiatric patients, 42% had schizophrenia, 36.7% were bipolar mood disorder and 21.3% had other type of disorders. BMI of 66.7% patients were normal, 22% below normal and 11.3% were above normal. Among all the patients 71.4% male and 60.6% female were normal by BMI, whereas 11.3% patients were over weight. Among the over weight patients, 6% were male and 18.2% were female. In the present study 22% patients were under weight, where 22.6% were male and 21.2% were female. Nutritional assessment showed 61.9% male patients and 63.64% of female patients had normal MAC. Maximum of patients (72%) were anemic clinically. Again according to marital status 74.1% married and 58% of unmarried patients were found normal by BMI. In the study, 66.7% schizophrenic patients and 65.5% BMD patients were found in normal BMI. DOI: 10.3329/taj.v22i1.5022 TAJ 2009; 22(1): 82-87